Effect of Plasmid Presence and Stability on Growth of Escherichia coli DH5Î± with Use of Drugs, Chemicals, and Radiation (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The purpose of the study delineates the growth and plasmid stability of E. coli DH5Î± host system.Materials and Methods: Different concentrations of drugs, chemicals, and various frequency of radiations weresubjected to the host system to verify the colony-forming units along with plasmid concentration and stability.Results: Among chemicals, acridine orange showed the highest effect on growth of DH5Î±, while among thedrugs, danthrone showed maximum effect on the growth of the organism. Radiofrequency of 2 GHz and lowintensitymicrowave radiation were recorded as the highest inhibitory effects. However, there is no significanteffect in growth observed in exposure to UV rays. Conclusion: The present work discussed that drugs, chemicals,radiofrequency, and microwave radiation have a huge effect on the growth of organism and also on the concentrationand stability of plasmid.